Zentrifugalkräfte in Europa und im sozialen Rechtsstaat: Festschrift für Klaus Tonner - Tamm, Marina (Nomos Verlagsgesellschaft mbH & Co. KG, 2022)
The Festschrift in honour of Prof. Dr. Klaus Tonner will be published on the occasion of his 75th birthday in autumn 2022. Friends, companions, colleagues and students have contributed to the Festschrift, which contains eighteen articles on German, European and international (consumer) law. The contributions of these authors contain a colourful compendium of current consumer policy challenges, ranging from very fundamental questions on the further development of the European agenda to concrete individual problems (regulation of supply chains, climate protection as a constitutional mandate, LegalTech, data protection, loan law, revocation, consumer arbitration and out-of-court redress, current issues of package travel law and market research). From the range of topics, the topicality and the balanced relationship between academic and practical relevance, this work can be characterised as comprehensive and fundamental and, in this respect, no consumer law library can be imagined without it. It contains many thought-provoking and highly topical issues.With contributions byStefanie Bergmann | Christof Berlin | Tobias Brönneke | Claire Feldhusen | Barbara von Finckenstein | Ernst Führich | Edgar Isermann | Wolfhard Kohte | Kai Korte | Thomas Krüger | Hans-W. Micklitz | Ralf Reichertz | Udo Reifner | Peter Rott | Patrick Schröder | Hans-Peter Schwintowski | Astrid Stadler | Ansgar Staudinger | Björn Steinrötter | Marina Tamm | Martin Tonner | Michael Zerres | Thomas Zerres